Bases of musical nationalism in Argentina (2nd part) - Fusco Morales, Andrea Gabriela (2024)
This collaboration is an adaptation to the format of a scientific article of the contents of my doctoral thesis on Nationalism in Argentina. It reflects on this movement in Argentine orchestral music and studies the ways in which composers expressed it in their works by incorporating elements from folklore, Indigenous music, and tango. For a study of the musical corpus, a selection of representative works by various composers of the period was made and analyzed based on the object of study. Links were established between the observed features and the characteristics of folk, Indigenous and urban popular music, focusing attention on the ways in which artists crafted these elements with European tools. The construction of nationalism is a conscious decision that involves political, historical, and cultural aspects. Towards the end of the 19th century and the first half of the 20th century, nationalism was prominent both in Argentina and in Latin America and other countries. The second part of my work, which is now presented here, constitutes an analysis of a group of emblematic works on which the nationalist movement in Argentina was built.